Extreme hyponatremia as a risk factor for early mortality after liver transplantation in the MELD‐sodium era. (7th October 2021) - Ivanics, Tommy; Leonard‐Murali, Shravan; Mouzaihem, Hassan; Moonka, Dilip; Kitajima, Toshihiro; Yeddula, Sirisha; Shamaa, Mhd Tayseer; Rizzari, Michael; Collins, Kelly; Yoshida, Atsushi; Abouljoud, Marwan; Nagai, Shunji
Summary: The impact of hyponatremia on waitlist and post‐transplant outcomes following the implementation of MELD‐Na‐based liver allocation remains unclear. We investigated waitlist and postliver transplant (LT) outcomes in patients with hyponatremia before and after implementing MELD‐Na‐based allocation. Adult patients registered for a primary LT between 2009 and 2021 were identified in the OPTN/UNOS database. Two eras were defined; pre‐MELD‐Na and post‐MELD‐Na. Extreme hyponatremia was defined as a serum sodium concentration ≤120 mEq/l. Ninety‐day waitlist outcomes and post‐LT survival were compared using Fine‐Gray proportional hazard and mixed‐effects Cox proportional hazard models. A total of 118 487 patients were eligible ( n  = 64 940: pre‐MELD‐Na; n  = 53 547: post‐MELD‐Na). In the pre‐MELD‐Na era, extreme hyponatremia at listing was associated with an increased risk of 90‐day waitlist mortality ([ref: 135–145] HR: 3.80; 95% CI: 2.97–4.87; P  < 0.001) and higher transplant probability (HR: 1.67; 95% CI: 1.38–2.01; P  < 0.001). In the post‐MELD‐Na era, patients with extreme hyponatremia had a proportionally lower relative risk of waitlist mortality (HR: 2.27; 95% CI 1.60–3.23; P  < 0.001) and proportionally higher transplant probability (HR: 2.12; 95% CI 1.76–2.55; P  < 0.001) as patients with normal serum sodium levels (135–145). Extreme hyponatremia was associated with a higher risk of 90, 180, and 365‐day post‐LT survival compared to patients with normal serum sodium levels. With the introduction of MELD‐Na‐based allocation, waitlist outcomes have improved in patients with extreme hyponatremia but they continue to have worse short‐term post‐LT survival. Abstract : With the introduction of MELD‐Na‐based allocation in the United States, waitlist outcomes (waitlist mortality and transplant probability) have improved in patients with extreme hyponatremia (≤120 mEq/l). However, these patients continue to have inferior short‐term post‐LT survival outcomes.